Population dynamics and spatial distribution of flatfish species in shrimp trawl bycatch in the Gulf of California - Carlos Hiram Rábago-Quiroz (Hidrobiológica, 2008)
By determining the specific composition, spatial distribution and population dynamics of flatfish species captured in shrimp trawls' bycatch in the Gulf of California, this study aims to contribute to the knowledge of bycatch fish population which has thus far been of little interest. Samplings were taken from shrimp trawls' in two fishing seasons (2002 and 2003) onboard shrimp fleets and also from two research cruises during closed shrimp season. The results showed 15 species of flatfish belonging to 5 families: Achiridae, Bothidae, Cynoglossidae, Pleuronectidae and Paralichthyidae. Paralichthyidae was the most abundant with 9 species. The range in sizes of these flatfish species varied in total length from 20 to 380 mm, with the most frequent sizes ranging from 60 to 180 mm and only a few species of the Paralichthys genera surpassing 250 mm in total length. The growth estimate parameter for the most abundant flatfish species varied according to the longevity of these species. More than 50 % of the organisms sampled were of small size, and the majority of these were captured before the sexual maturity which may have caused a potential effect on the population; however the consequences of this action on the population are unknown.